Experimental estimates of Indigenous employment from administrative data - Kapuscinski, Cezary; Thomson, Kyle (My University, 2014)
In this paper we test a ‘proof of concept’ to remedy the lack of timely data on Indigenous labour market outcomes. The project uses Centrelink administrative data and the HILDA survey to estimate the employment to population ratio of Indigenous Australians. In doing so we examine the probabilities of income support recipients and the wider population transiting from one labour market state to another and create experimental time-series estimates of employment to population ratio of Indigenous Australians.
Keywords: Employment; Disadvantage; Culture -- Indigenous; Labour market; Disadvantage; Culture; Employment; Indigenous; Employment and unemployment